2019
DOI: 10.1111/and.13239
|View full text |Cite
|
Sign up to set email alerts
|

Methylation levels ofIGF2andKCNQ1in spermatozoa from infertile men are associated with sperm DNA damage

Abstract: Abnormal imprinted genes methylation in spermatozoa has been shown to be associated with subfertility. However, the relationship between sperm DNA damage and specific imprinted genes methylation remains unclear. In this study, DNA methylation levels were determined at seven imprinted genes loci (H19, INS‐IGF2, KCNQ1, MEG3, MEST, PEG3 and SNRPN) in 66 semen samples using the MSRE‐qPCR method. The semen samples were divided into two groups according to the threshold value (25%) of DNA fragmentation index (DFI). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 71 publications
0
10
0
1
Order By: Relevance
“…Accordingly, ROS have been found capable of altering H19-Igf2 methylation (by reducing H19 and increasing Igf2 methylation pattern) [32]. Moreover, abnormal methylation of the imprinted genes IGF2 and KCNQ1 at the spermatozoon level has recently been reported in infertile patients, in association with an increased sperm DNA fragmentation [33]. Furthermore, global sperm DNA methylation has been shown to inversely correlate with sperm DNA fragmentation [34].…”
Section: Sperm Genomementioning
confidence: 99%
“…Accordingly, ROS have been found capable of altering H19-Igf2 methylation (by reducing H19 and increasing Igf2 methylation pattern) [32]. Moreover, abnormal methylation of the imprinted genes IGF2 and KCNQ1 at the spermatozoon level has recently been reported in infertile patients, in association with an increased sperm DNA fragmentation [33]. Furthermore, global sperm DNA methylation has been shown to inversely correlate with sperm DNA fragmentation [34].…”
Section: Sperm Genomementioning
confidence: 99%
“…However, other studies exploring the methylation levels of IGF2 in spermatozoa offer inconclusive data. Ni et al 18 associated lower IGF2 methylation levels with higher sperm DNA fragmentation (negative correlation), whereas Darbandi et al 46 positively correlated these with ROS levels. Additionally, ROS levels were positively correlated with the DNA fragmentation index 46 .…”
Section: Discussionmentioning
confidence: 99%
“…The field of human reproduction is no exception in following this trend, as studying epigenetic changes in gametes is even more interesting considering that gametes are responsible for transferring genetic material to the next generation 11 . Lately, a number of studies exploring sperm DNA methylation from different angles have been published, 12‐18 but there is a lack of studies on how different sperm preparation methods could possibly influence the sperm DNA methylation profile. To our knowledge, only one study has explored the DNA methylation profile of spermatozoa after DGC sperm preparation, 22 which is one of the most often used sperm preparation method in assisted reproduction 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poplinski et al [29] conclude that low sperm counts were clearly associated with IGF2/H19 ICR1 hypomethylation, and idiopathic male infertility was strongly associated with imprinting defects at IGF2/H19 ICR1. Ni et al [30] indicated that the aberrant methylation of IGF2 and KCNQ1 gene may be associated with sperm DNA damage. Tang et al [31] revealed that miR-210 was involved in spermatogenesis by targeting IGF2 in male infertility.…”
Section: Discussionmentioning
confidence: 99%